Student protests in South African universities with specific reference to Rhodes University (1970-1994) - Gillam, Katherine Elaine (Rhodes University, Faculty of Humanities, Department of History)
This thesis is about student protest at Rhodes University from 1970- 1994 It examines how student protests mirrored broader political and economic contexts in this period. Further this thesis also investigates the changes in student protest over the years. As democracy drew closer, student protests at Rhodes became less apparent. This thesis consults numerous sources which include books, articles, archives and extensive interviews. A significant aspect of this work is that the research on the Black Students Movement at Rhodes University has not been explored in detail, particularly in scholarly works. This thesis therefore contributes to the historiography of black student politics at a historically white university. It also explores the period of democratic transition in South Africa, where secondary issues such as gender and access came to the forefront of student protests. As democracy drew closer, student protests became infrequent on campus due to the changes anticipated under the newly elected democratic government. Despite sparse protests, black students remained sceptical of the democratic transition. The thesis uncovers that many issues were left unresolved which later resurfaced under the 2015 and 2016 #RhodesMustFall, #FeesMustFall and #RUReferenceList protests.
Keywords: Student movements -- South Africa -- Makhanda History; Students Political activity -- South Africa -- Makhanda; College students, Black Political activity -- South Africa -- Makhanda; Rhodes Must Fall; FeesMustFall; South Africa Politics and government 1994-; Democratic transition